Optimizing Quranic Learning for the Elderly: An Integrative Religious Experience Model to Enhance Spiritual Wellness in Pesantren Communities - Khoirun Nasihin; Mochamad Hasyim; Ahmad Aris Fajarudin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: The increasing elderly population presents a challenge in meeting their psychosocial and spiritual needs. Learning the Quran in later life is often hindered by methods that are not age-friendly, leading to social isolation and reduced spiritual well-being. Purpose of the Study: This program was designed to implement a Religious Experience Learning (REL) approach to address three core issues: developing a suitable pedagogical method, enhancing access and participation through effective mentoring, and ultimately strengthening the spiritual wellness of elderly participants. Methods: The program employed a Service Learning methodology, structured in three stages: preparation, implementation (participatory REL-based learning, and reflection. The REL framework integrated technical (Bagdadi method), reflective (contextual hermeneutics), and spiritual (contemplative practice) dimensions. Results: The program achieved holistic transformation. Methodologically, a shift to humanistic approaches created a psychological safety and increased intrinsic motivation. Socially, a multi-generational community and empathetic mentoring reduced isolation. The primary outcome was enhanced spiritual wellness, evidenced by the personalization of worship, internalization of Quranic values as a life framework, and the achievement of eudaimonic well-being marked by inner peace (sakinah), self-acceptance, and a profound sense of meaning in life.